Numerical simulation of heterogeneous material failure by using the smoothed particle hydrodynamics method - Wang, Xuejun (2009)
Many numerical methods have been proposed in the efforts to revel the failure mechanism of the brittle materials, such as rock and concrete, under various loading conditions. It is of continuous interests on properly modeling the heterogeneous microstructure and to account for its effects on the macroscopic material failure; and effectively tackling the initial and created discontinuities, such as fractures and fragmentations in the failure process. In this thesis, a numerical approach based on the mesh-free Smoothed Particle Hydrodynamics (SPH) method is developed that is able to simulate the dynamic failure of brittle materials by capturing the detailed occurring sequence of the microscopic cracks as well as the macro mechanical response. An elasto-plastic damage model based on the extension of the Unified Strength Theory is adopted in order to better reflect the strength behavior of the materials. To model the material heterogeneity, a statistical approach has been utilized. In addition, a polymineral model for the multi-phased materials has been incorporated to simulate heterogeneous materials with different compositions more appropritely. A series of numerical simulations in 2-D and 3-D on rock-like material failures are performed using the developed program. The influences of material heterogeneity as well as the strain rate on the material fracture process and its dynamic strength are investigated and compared with experimental results. Comparisons show that they agree well qualitatively. Particularly, the results reveal that the strain rate dependency of the dynamic tensile and compressive strength might be ascribed to the apparent confining pressure effects by the rapid loading. It shows that the developed program is very promising in conducting such kind of simulations and deserves further improvements for many other applications.